Increasing injectable Fe (GleptoForte) in newborn piglets - Salgado, Briana; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Anemia in newborn piglets is an issue as it decreases production due to severe growth impairment. Variable dosages of GleptoForte were analyzed to determine the effects on nursing piglets through collection of blood and growth criteria. A total of 336 piglets: 28 liters, 12 pigs per litter, 56 pigs per treatment, were given one of the six experimental treatments. Fe injections of GleptoForte were given on d3 post farrowing. Dosages included 1) a control at 0mg, 2) 50mg, 3) 100mg, 4) 150mg, 5) 200mg, or 6) 200mg on d3 with a following 100mg on d11 of GleptoForte. Blood criteria included: Hemoglobin, Hematocrit, Serum Fe, and TIBC and were collected on day of processing (d0), d11, and d21. Observation of growth criteria from d3 to d11, to d21 showed ADG and BW improving (P=0.001) as the dosage of GleptoForte increased. This trend excludes the 6th treatment (200mg on d3 with a booster of 100mg on d11) which did not show a significant improvement (P=0.001) in comparison to the 5th treatment (200mg of GleptoForte) for either ADG or BW criteria. Hemoglobin (Hgb) levels observed from d3 to d21 blood samples did not show a common trend. Despite this, Hgb did show increasing (P=0.001) levels with 150mg or higher dosage including treatment 6, across d3 to d21. Blood samples gathered from d21 alone showed an increasing (P=0.001) trend with increasing dosages. Hematocrit (Hct) levels from blood samples were similar to that of the trend from Hgb levels which showed no improvement (P=0.001) from d3 to d21 until 150mg of GleptoForte. D21 Hct specifically showed increasing (P=0.001) levels as the dosage increased. Treatment 6 showed significant benefits (P=0.01) compared to treatment 5. Serum Fe levels addressed from d3 to d21 showed no increasing (P=0.001) trends. However, Serum Fe levels did increase (P=0.001) as GleptoForte dosage increased. Serum Fe levels on d21 also showed significant benefits (P=0.001) from treatment 6 compared to treatment 5. Finally, Total Iron Binding Capacity (TIBC) showed increasing (P=0.001) levels from d3 to d21 for each treatment. Despite this, there were no common trends between the values as dosages increased at any given day blood samples were taken. In conclusion, 200mg+100mg of GleptoForte improved Hemoglobin and Hematocrit criteria, but showed no increasing improvement compared to 200mg alone.
Keywords: Fall 2017